The official ACT prep guide : (Wiley, 2017)
he book contains information on how to register for the exam, proven test-taking strategies, ideas for preparing mentally and physically, gearing up for test day, and much more. This invaluable guide includes additional questions and material that contains articles on everything from preparing a standout college application and getting into your top-choice school to succeeding in college